Prospective analysis and influence of social entrepreneurship in development in catatumbo, Norte de Santander, Colombia (2018)
The aim of this study was both, to address a prospective analysis and to study the influence of social entrepreneurship in the development of Catatumbo sub-region from Norte de Santander, Colombia. The context OS this study was explored to address prospective events and scenarios identifying action´s lines related with departmental and national development plans. Social entrepreneurship was approached as a basis of endogenous development from society actor articulation. In order to achieve these purposes, a qualitative research approach was adopted based on the phenomenological method by means of documentary analysis, application of 26 in-depth interviews in 15 inhabitants and 11 mayors of this sub-region and, finally by non-participating observation method. The research process revealed two foundation categories for this study: the prospective and social entrepreneurship split in internal (15) and external subcategories (20), which delineate the prospective scenarios with their respective events and concentration rates. The findings suggest that spaces should be generated with the aim to encourage public policies linking all society sectors through the establishment of a sustainable economic development framework based on the social entrepreneurship, by networks, marketing channels, productive associations and product innovation promotion (among other aspects derived from the prospective application) for value generation of social transformation in the regions affected by violence as is the case exposed in the present study.